Engineered nanoceria modulate neutrophil oxidative response to low doses of UV‐B radiation through the inhibition of reactive oxygen species production. Issue 12 (26th June 2021) - Peloi, Karen Elaine; Ratti, Bianca Altrão; Nakamura, Celso Vataru; Neal, Craig J.; Sakthivel, Tamil Selvan; Singh, Sushant; Seal, Sudpita; de Oliveira Silva Lautenschlager, Sueli
Abstract: To avoid aging and ultraviolet mediated skin disease the cell repair machinery must work properly. Neutrophils, also known as polymorphonuclear leukocytes, are the first and most abundant cell types which infiltrate sites of irradiation and play an important role in restoring the microenvironment homeostasis. However, the infiltration of neutrophils in ultraviolet‐B (UV‐B) irradiated skin might also contribute to the pathophysiology of skin disease. The polymorphonuclear leukocytes activation induced by UV‐B exposure may lead to prolonged, sustained NADPH oxidase activation followed by an increase in reactive oxygen species (ROS) production. Our previous work showed that cerium oxide nanoparticles can protect L929 fibroblasts from ultraviolet‐B induced damage. Herein, we further our investigation of engineered cerium oxide nanoparticles (CNP) in conferring radiation protection specifically in modulation of neutrophils' oxidative response under low dose of UV‐B radiation. Our data showed that even low doses of UV‐B radiation activate neutrophils' oxidative response and that the antioxidant, ROS‐sensitive redox activities of engineered CNPs are able to inhibit the effects of NADPH oxidase activation while conferring catalase and superoxide dismutase mimetic activity. Further, our investigations revealed similar levels of total ROS scavenging for both CNP formulations, despite substantial differences in cerium redox states and specific enzyme‐mimetic reaction activity. We therefore determine that CNP activity in mitigating the effects of neutrophils' oxidative response, through the decrease of ROS and of cell damage such as chromatin condensation, suggests potential utility as a radio‐protectant/therapeutic against UV‐B damage.